Inside Back Cover: Suzuki–Miyaura Diversification of Amino Acids and Dipeptides in Aqueous Media (ChemCatChem 14/2015). Issue 14 (13th July 2015) - Willemse, Tom; Van Imp, Karolien; Goss, Rebecca J. M.; Van Vlijmen, Herman W. T.; Schepens, Wim; Maes, Bert U. W.; Ballet, Steven
<x xml:space="preserve">Abstract</x> The Inside Back Cover picture shows palladium‐catalyzed derivatisations of halogenated phenylalanine and tryptophan and dipeptide substrates containing these entities in view of the optimization of lead peptide ligands for improved receptor interactions. A wide scope of substrates is presented to highlight the tolerated peptide functionality during the application of the Suzuki‐Miyaura reaction in aqueous media. In their Full Paper, T. Willemse et al. investigate the influence of unprotected peptide functionalities on the progress of the Pd‐catalyzed reaction. In the background, the collaboration between the Maes and Ballet laboratories is emphasized by the skylines of Antwerp and Brussels. The article highlighted by this cover can be found on p. 2055 ff. of Issue 14, 2015.